0596 Impact of Obstructive Sleep Apnea on Clinical Outcomes in Acute Coronary Syndrome. (27th April 2018) - Baba, R Y; Soma, D; Sediqe, S; Kondapaneni, M; Auckley, D
Abstract: Introduction: Elucidating the effects of obstructive sleep apnea (OSA) on cardiovascular outcomes in acute coronary syndrome (ACS) is crucial in risk assessments and therapeutic recommendations for affected individuals. Methods: In this prospective, observational, single center study, patients admitted for ACS (ST segment elevation (STEMI), non-ST segment elevation (NSTEMI) and unstable angina (UA)), who have coronary revascularization during the admission are undergoing inpatient overnight sleep studies using a level III portable diagnostic device (ApneaLink). Patients older than 18 years are eligible. The subjects are divided into 2 groups based on apnea-hypopnea index (AHI): OSA (AHI≥15) and non-OSA (AHI<15). The primary endpoint of this study is 30-day major adverse cardiovascular events (MACE), a composite endpoint of cardiovascular death, non-fatal MI, stroke and need for unplanned repeat revascularization. Secondary endpoints include individual MACE outcomes, heart failure (HF) requiring rehospitalization, and all-cause mortality. Results: Between August 29, 2017 and November 30, 2017, 21 eligible patients have been enrolled and successfully undergone an overnight sleep study. Of these 21, 13 patients (mean age 54.5 ± 12.5 years, Male % 57.1, BMI 32.1 ± 8.1 kg/m 2 ) have had adequate sleep study data. 30-day follow up outcomes are available in 11 patients to date. Of the 13 patients with sleep study data, there were 7 NSTEMI, 4 STEMI and 2 UA, with 9 undergoing percutaneous intervention and 4 requiring coronary artery bypass. OSA defined as an AHI≥15 has been found in 53.8% patients, with a mean AHI of 27.1 ± 10.0 in the OSA group vs. 5.6 ± 2.5 events/hour in the non-OSA group. ESS, STOP-BANG, and Berlin Questionnaire scores were higher in the OSA group. Only one 30-day MACE event (unplanned revascularization) has occurred in a patient in the OSA group, and none have occurred in the non-OSA group. Patients in the non-OSA group were more likely to be diagnosed with HF and cardiogenic shock during the hospitalization. Conclusion: Preliminary data finds a high rate of OSA in patients admitted with ACS. A larger sample size is being recruited to identify any significant differences in the primary endpoints. Support (If Any): None.